Coarse Hierarchical Delta Debugging - Hodovan, Renata; Kiss, Akos; Gyimothy, Tibor (ICSME 2017 : proceedings : 2017 IEEE International Conference on Software Maintenance and Evolution : 19-22 September 2017, Shanghai, China, 2017)
This paper introduces the Coarse Hierarchical Delta Debugging algorithm for efficient test case reduction. It can be used as a test case simplification algorithm in its own right if theoretical minimality is not a strict requirement, or it can act as a preprocessing step to the original Hierarchical Delta Debugging algorithm. Evaluation of artificial and real test cases shows that a coarse variant can produce reduced test cases with significantly fewer testing steps than the original algorithm (58% gain on average, 79% maximum), while still keeping the outputs acceptably small (never increasing the reduced test cases by more than 0.36% of the input).